Strategic plan for Creamás - Oliveros Lijap, Luis Alfredo (2015)
The purpose of this research is to develop a 2015-2020 Strategic plan for Creamás, a Peruvian NGO that fosters the dreams and ambition of children through education and diverse workshops. The company began operating in the country in 2009 and throughout the years has managed to become a referent in the NGO national industry. In order to do that the model proposed by Fernando D’Alessio was followed throughout the nine chapters of the document. After thorough research, meetings with the directorates and volunteers, and on-site visitation, data was analyzed in an attempt to decipher the current holistic situation of the organization; its strengths, weaknesses and which opportunities and threats the external situation posed the organization. By complementing such information with a newly proposed vision and mission, and the identified organization’s interests; six long term objectives were defined with their correspondent short-term objectives. Besides that, five strategies were chosen in order for the Creamás to achieve its objectives and as a consequence, its desired vision. Furthermore, in order for Creamás to assess the implementation of this Plan, the document includes the proposed Balanced Scorecard; with the short-term objectives and their correspondent indicators. The fallouts of this work indicate that currently Creamás lacks operational efficiency due to the poor training of its volunteers, is still unable to measure its actual impact on the students, and does not possess a solid funding structure; all of them a must if the firm is to remain relevant in the industry